The Affirmative Action For Women In Legislative Elections As An Effort To Embody Inclusive Regulations - Coloay, Juneidi D (IBLAM LAW REVIEW, 2026)
This study aims to examine the concept of guaranteeing women's political rights and the importance of women's representation in the formation of inclusive regulations. Based on normative legal research, this article attempts to present doctrinal and fundamental arguments using literature review techniques. The results show that, first, women's political rights in filling legislative positions have been guaranteed in the election law in the form of a quota system for legislative candidate representation of at least 30 percent; second, women's representation in parliament can encourage the formation of inclusive regulations because the quantity of women might influence decision-making in parliament.